Polyfluoroalkyl compounds in the marine environment – Investigations on their distribution in surface water and temporal trends in harbor seals (phoca vitulina) - Ahrens, Lutz (2010)
Recently polyfluoroalkyl compounds (PFCs) were discovered as emerging persistentorganic pollutants. Because of their unique physicochemical properties due to theircombination of lipophilic and hydrophilic characteristics, PFCs have been widely used inmany consumer products, such as polymerisation aids, stain repellents on carpets, textiles, andpaper products for over 50 years. From the production and use of these products, PFCs can bereleased into the environment. Scientific concern about PFCs increased due to their globaldistribution and ubiquitous detection in the environment, especially in marine mammals.An analytical protocol was developed for the analysis of PFCs in water samples andvarious biological matrices. The samples were analysed for 40 PFCs plus 20 isotope-labelledinternal standards using high performance liquid chromatography/negative electrosprayionisation-tandem mass spectrometry (HPLC/(-)ESI-MS/MS). Furthermore, the analyticalquality of the laboratory has been approved in interlaboratory studies.In the first part of this Ph.D. thesis was investigated the occurrence, distribution patternand transportation mechanisms of PFCs in seawater. The rivers had a high influence on thedistribution of PFCs in offshore surface water in the German Bight, with decreasingconcentrations with increasing distance from the coast (see publication I). The research onthe spatial distribution of PFCs in coastal area is very important for the understanding of thetransportation and fate of PFCs in the marine environment. Furthermore, the longitudinal andlatitudinal distribution of PFCs in surface water of the Atlantic Ocean was investigated (seepublication II). The results indicate that trans-Atlantic Ocean currents caused the decreasingconcentration gradient from the Bay of Biscay to the South Atlantic Ocean and theconcentration drop-off close to the Labrador Sea. These data are very useful for globaltransportation models, in which industrial areas are considered as sources, and ocean watersas sinks of PFCs.The second ...